Lesson study dengan penilaian kinerja dalam praktik lapangan konseling kelompok untuk meningkatkan kemampuan mahasiswa calon konselor - Kadek Suranata; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to improve the ability to manage the practice of group counseling in students through a Lesson Study with performance assessment. The subjects of this study were 42 students in the Guidance and Counseling department. This research was conducted with lesson study in three cycles, each cycle consisting of two meetings of practical activities in schools in the stages of the plan, do and see. Lesson study activities were carried out in three secondary schools in Singaraja, Bali, involving school counselors as observers and supervisors. The data in this study in the form of student learning outcomes of group counseling practice were obtained through performance assessment with a guided observation method using the rubric of assessing skills in managing group counseling. The data in this study were analyzed descriptively quantitatively, then compared with the criteria for the success of the action using a reference on a scale of five. The results showed that the application of the lesson study method with performance assessments in group counseling practices has increased the ability of prospective counselor students in group counseling practices. The results of this study recommend the implementation of a lesson study with performance assessment as a model for improving the ability to manage group counseling for prospective counselor students.